Analisis Nilai Ekonomi dan Frekuensi Kunjungan Wisatawan pada Wisata Lembah Harau Sebelum dan Setelah Pandemi Covid-19 - Derizal Derizal (Ekonomis: Journal of Economics and Business, 2023)
The Harau Valley as one of the tourist attractions in the Lima Puluh Kota Regency, West Sumatra that cannot be denied its beauty. In 2016-2020 the Harau Valley tourist attraction among other tourist objects in the Lima Puluh Kota Regency achieved the number of visits that were most visited by tourists, but there was a phenomenon when COVID-19 occurred (January 2019-December 2020 Period). This study aims to analyze the frequency of visits and the economic value of tourists on Harau Valley tourism before and after the COVID-19 pandemic. The method used in this study is multiple analysis reggression to identify factors that influence the frequency of visits and travel costs to identify economic value. The results show that the total cost has a significant negative effect on the frequency of visits in the Harau valley, while distance, worship facilities and beauty significantly positively affect the frequency of visits by tourists to the Harau valley before the COVID-19 pandemic, and other variables are not significant. Service satisfaction has a positive influence on the frequency of visits in the Harau Valley, while other variables that do not significantly affect the frequency of COVID-19. Valuation economic befor COVID -19 are greater than after the COVID-19 pandemic. Where there is a decrease of Rp. 5,509,000,000, / year.